Novelties in Asian Mitreola (Loganiaceae): M. capitata, a new species from Vietnam, and lectotypification of M. spathulifolia - Nuraliev, Maxim S.; Lyskov, Dmitry F.; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Fu, Long-Fei (Phytotaxa, 2023)
Mitreola capitata, a new species of Loganiaceae, is described and illustrated. The species was discovered in 2022 during a botanical survey of Phong Nha-Ke Bang National Park (Quang Binh Province, northern Vietnam), where it inhabits a steep limestone rock. Mitreola capitata is remarkable for its habit that includes a leaf-rosette, compact head-like inflorescence with long peduncle and prominent indumentum of most plant parts. The new species is most similar to M. spathulifolia, differing by smaller leaves, dense and compact inflorescence, shorter pedicel, hairy calyx and smaller capsule. Typification of M. spathulifolia is revised, and a lectotype is selected.